Chronic HCV infection promotes cytotoxicity in antigen-specific CD8+ T cells regardless of virus specificity - Maretti-Mira, Ana C.; Salomon, Matthew P.; Hsu, Angela M.; Matsuba, Chikako; Golden-Mason, Lucy (Frontiers in Virology, 2023)
Introduction: Despite advancements in hepatitis C virus (HCV) infection treatment, HCV still represents a significant public health burden. Besides progressive hepatic damage, viral persistence has lasting effects on innate and adaptive immune responses. Lack of a complete understanding of the factors driving an effective HCV response contributes to the failure to develop a vaccine for prevention. This study advances the existing knowledge on HCV-specific CD8+ T cells and describes the impact of current or past HCV infection on CD8+ T cells specific for other viruses. Methods: We used barcoded-dextramers to identify and sort CD8+ T cells specific for HCV, cytomegalovirus, and influenza, and characterized them using single-cell RNA sequencing technology. Our cohort included chronic (cHCV), spontaneously resolved (rHCV), and subjects undergoing direct-acting antiviral (DAA). Results: We show that HCV-specific CD8+ T cells have cytotoxic features in patients with cHCV, which is progressively reduced with DAA therapy and persists 12 weeks after treatment completion. We also observe a shift in the CD8+ T cell phenotype on DAA treatment, with decreased effector memory and exhausted cell signatures. In rHCV, we also detected a smaller proportion of effector memory cells compared to cHCV. The proportion of CD8+ exhausted T cells in cHCV and rHCV subjects was comparable. Moreover, we also observed that non-HCV virus-specific CD8+ T cells exhibit robust cytotoxic traits during cHCV infection. Discussion: Altogether, our findings suggest that chronic HCV infection promotes cytotoxicity in CD8+ T cells regardless of virus specificity. The immunological changes caused by cHCV infection in CD8+ T cells may contribute to worsening the ongoing hepatic damage caused by HCV infection or exacerbate the immune response to possible co-infections. Our data provide a resource to groups exploring the underlying mechanisms of HCV-specific T cell spontaneous and treatment-induced resolution to inform the development of effective vaccines against HCV infection.